Concerted regulation of mitochondrial and nuclear non‐coding RNAs by a dual‐targeted RNase Z. (20th August 2018) - Siira, Stefan J; Rossetti, Giulia; Richman, Tara R; Perks, Kara; Ermer, Judith A; Kuznetsova, Irina; Hughes, Laetitia; Shearwood, Anne‐Marie J; Viola, Helena M; Hool, Livia C; Rackham, Oliver; Filipovska, Aleksandra
Abstract: The molecular roles of the dually targeted ElaC domain protein 2 (ELAC2) during nuclear and mitochondrial RNA processing in vivo have not been distinguished. We generated conditional knockout mice of ELAC2 to identify that it is essential for life and its activity is non‐redundant. Heart and skeletal muscle‐specific loss of ELAC2 causes dilated cardiomyopathy and premature death at 4 weeks. Transcriptome‐wide analyses of total RNAs, small RNAs, mitochondrial RNAs, and miRNAs identified the molecular targets of ELAC2 in vivo . We show that ELAC2 is required for processing of tRNAs and for the balanced maintenance of C/D box snoRNAs, miRNAs, and a new class of tRNA fragments. We identify that correct biogenesis of regulatory non‐coding RNAs is essential for both cytoplasmic and mitochondrial protein synthesis and the assembly of mitochondrial ribosomes and cytoplasmic polysomes. We show that nuclear tRNA processing is required for the balanced production of snoRNAs and miRNAs for gene expression and that 3′ tRNA processing is an essential step in the production of all mature mitochondrial RNAs and the majority of nuclear tRNAs. Synopsis: This study shows that ELAC2 is required in mitochondria and in the nucleus for the correct processing of tRNAs, balanced production of non‐coding RNAs, assembly of ribosomes and efficient protein synthesis. ELAC2 is essential for nuclear and mitochondrial tRNA processing. Nuclear tRNA processing is essential for balanced production of other non‐coding RNAs. In mitochondria 3′ tRNA processing is preceded by 5′ tRNA cleavage. Abstract : This study shows that ELAC2 is required in mitochondria and in the nucleus for the correct processing of tRNAs, balanced production of non‐coding RNAs, assembly of ribosomes and efficient protein synthesis.